The impact of taxpayer education on tax compliance in South Africa. - Misra, Roshelle. (2011)
The South African economy is faced with the existence of a sophisticated industrial economy alongside an informal sector that is not properly regulated. As a result of poor and delayed compliance from the taxpaying population, a need arose to educate our society on their social responsibility to pay their taxes. This study is aimed at identifying the impact of tax education on tax compliance. The study endeavours to bridge the tax gap and engender a tax culture, by balancing the education and enforcement functions. === Thesis (M.Com.)-University of Kwazulu-Natal, 2004.